A novel approach to PFC for nonlinear systems - Rossiter, John Anthony; Aftab, Muhammad Saleheen; Panoutsos, George; González-Villarreal, Oscar J. (Elsevier, 2022)
This paper proposes a computationally efficient predictive control law for non-linear systems, that is one that can easily be coded and implemented on low cost hardware. Moreover, it has a secondary core benefit that the core tuning parameter reduces to a single choice which is: how much faster than open-loop would you like the closed-loop to converge? Conceptually the approach builds on the PFC approach but proposes a very different type of coincidence condition which removes the lag associated to the conventional approach. Simulations demonstrate that for some non-linear systems this is a cheap and simple way of ensuring effective feedback, with constraint handling.
Keywords: Predictive functional control; Computational efficiency; Transparent tuning; Nonlinear systems